What's in Your Teaching Toolbox? - Mormer, Elaine (Seminars in Hearing, 2018)
Educators are faced with an array of tools available to enhance learning outcomes in the classroom and clinic. These tools range from those that are very simple to those that are sufficiently complex to require an investment in learning time. This article summarizes a collection of teaching tools, ordered by the time involved in learning proficient use. Simple tools described include specific online blogs providing support for faculty and student writing and a simple method to capture and download videos from YouTube for classroom use. More complex tools described include a Web-based application for custom-created animated videos and an interactive audience polling system. Readers are encouraged to reflect on the tools most appropriate for use in their own teaching toolbox by considering the requisite time to proficiency and suitability to address desired learner outcomes.
Keywords: Teaching tools; interactive polling; Prezi; PollEverywhere; SQF Model